Physical and psychological abuse and self-assertiveness in children of educational institutions of rural area in the town of Huancavelica 2010 - Huamán Albites , Margarita Isabel (2020)
OBJECTIVE: To determine the relationship between the physical, psychological self-esteem and assertive- ness in children Educational Institutions in rural areas of the Parish of Huancavelica District 2010. METHODS: A quantitative, descriptive level, corre- lational design, descriptive methods, inductive -deduc- tive, population 22 students, non-probability sampling criterial. RESULTS: 45.5 % were boys and 54.5 % girls. 40.9 % suffered severe physical abuse, of which 4.5 % had high self esteem, high self-esteem trend 18.2 % , 13.6 % tendency to low self esteem and low self-esteem 4.5 % . The 13.6 % of physically abused , 3.6 % were moderate, of which 4.5 % had a tendency toward high self-esteem , self-esteem at risk, prone to low self-es- teem , 45.5% of children abused 31.8% showed a ten- dency to high self-esteem , self-esteem at risk 47.5 % and 9.1 % tendency to low self esteem. The victims of severe physical abuse , showed a 40.9 % average asser- tiveness and moderate physical abuse showed a high assertiveness 4.5 % and 9.1 % average , children who were not physically abused victims showed high asser- tiveness 31.8 % and 13.6 % average . The 13.6 % su- ffered psychological abuse both mild and moderate and 27.3 % severe. The victims of severe emotional abuse18.2 % showed high self-esteem trend, 4.5 % self at risk and prone to low self-esteem. Victims of psycholo- gical abuse showed moderate 4.5 % trend high esteem and low self-esteem 9.1 % trend and victims of psy- chological abuse showed slight trend 9.1 % and 4.5 % high esteem low self esteem trend, the results show that victims of severe psychological abuse showed a asser- tiveness of 4.5 % at high and 22.7 % average, moderate psychological abuse victims showed a 13.6 % average assertiveness and psychological abuse victims showed mild assertiveness 9.1 % higher and 4.5 % medium. CONCLUSIONS: Children (as) were victims of severe physical abuse at a higher rate, being a low percentage of children (as) with a tendency to low self esteem and low self-esteem, also showed a higher percentage of as- sertiveness on the middle level. Victims of psychologi- cal abuse in different categories , showed a fluctuating trend esteem between high self-esteem and a low self esteem, assertiveness regarding showed a medium le- vel. Nonparametric statistical test Chi-square, p = 0.05, concluding that there is significant association between physical abuse and level of assertiveness, with p = 0.007. It also found evidence to say that there is signifi- cant association between psychological abuse and level of assertiveness p = 0.194. In tale of physical abuse and self-esteem with a p = 0.551; notes that no significant relationship between the study variables . Finally in ter- ms of psychological abuse and self-esteem with a p =0.914, it is evident that there is significant relationship between the study variables.